“A reinstilled hope that they can change”: Facilitator perspectives on a self-care and health promotion peer group program for veterans - Richard, Bonnie O.; Abadi, Melissa H.; Drake, Connor D.; Rychener, David; Bauer, Rachel (Frontiers in Public Health, 2023)
Introduction This study assessed the relevance, value, and effectiveness of “Taking Charge of My Life and Health” (TCMLH), a patient wellbeing peer group program for U.S. veterans focused on empowering them to identify what really matters in their lives and to work toward health goals that align with their mission, aspirations, or purpose in life. The potential of TCMLH to empower veterans to engage in self-care behaviors, make health behavior changes, and participate in health care decision making is important, as veterans are more likely than the general population to suffer from multiple chronic conditions that require ongoing self-management. Methods We conducted individual semi-structured interviews with 19 TCMLH facilitators serving in eight U.S. Veteran's Health Administration medical centers. Data were analyzed using an inductive approach to identify salient themes in facilitators' experiences. Results Facilitators reported that TCMLH participants demonstrated positive attitude changes (e.g., greater confidence and hope) and behavior changes (e.g., making healthcare appointments and implementing self-care practices) by program completion. Further, findings show that mindful awareness practices, the peer group setting, Whole Health assessment tools, and goal setting tools were perceived as the most impactful program elements leading to positive health behavior change. Conclusion Overall, findings suggest that this non-clinical peer group program can enhance patient wellbeing, and that there are certain program elements of TCMLH that are driving key attitudinal and behavioral changes.